STUDY OF ANTIOXIDANT CAPACITY IN WINE RED VALLEY ICA - Felices V., Leslie M. (2005)
lt has been evaluated the antioxidant activity «In Vitro» of its wines and the quantity of total polyphenols. The samples evaluated of red wine come from three prestigious wine cellars of lca's Valley like they are: Wine Cellar Tacama, Wine Cellar Vista Alegre and Wine Cellar Ocucaje. The analytical methods used to evaluate the antioxidant activity based on its capacity to catch radical free, !he use of !he radical 2,2-Difenil-1-picril hidracilo (test of !he DPPH). For !he determination of the total polyphenols was applied Folín Ciocalteu's method. Additionally determined different parameters in sample of wines that comes of Wine Cellar Tacama. The obtained values demonstrate that the wine named «Special Selection» of Wine Cellar Tacama presents a majar antioxidant capacity whose variety of grape corresponds to Tannat and Petit Verdot. In conformity to it, the quantity of total polyphenols analyzed in !he different samples found in majar concentration in the wine «Special Selection».